Selectively Enhanced Development of Working Memory in Musically Trained Children and Adolescents - Saarikivi, Katri Annukka; Huotilainen, Minna; Tervaniemi, Mari; Putkinen, Vesa (Frontiers in Integrative Neuroscience, 2019)
In the current longitudinal study, we investigated the development of working memory in musically trained and nontrained children and adolescents, aged 9-20. We measured working memory with the Digit Span (DS) forwards and backwards tests (N=106) and the Trail-Making A and B (TMT-A and B) (N=104) tests three times, in 2011, 2013, and 2016. We expected that musically trained participants would outperform peers with no musical training. Indeed, we found that the younger musically trained participants in particular outperformed their nontrained peers in the TMT-A, TMT-B and DS forwards tests. These tests all primarily require active maintenance of a rule in memory or immediate recall. In contrast, we found no group differences in the backwards test that requires manipulation and updating of information in working memory. These results suggest that musical training is more strongly associated with heightened working memory capacity and maintenance than enhanced working memory updating, especially in late childhood and early adolescence.